Calcium Treatment Against Anthracnose and Brown Rot in Red Dragon Fruit [Hylocereus Polyrhizus (F.A.C. Weber) Britton & Rose] - Abd. Ghani, Muhd. Azlan (2010)
Dragon fruit (Hylocereus polyrhizus) is a non-climacteric fruit, normally harvested at a full maturity stage (index five) in order to get the best marketing quality. Harvesting at such stage shortens storage life and renders the fruit more susceptible to disease infection. This study was designed to test the possible beneficial effects of calcium (Ca) on fruit quality as well as on the occurrence of anthracnose (caused by Collectotrichum gloeosporioides) and brown rot (caused by Monilinia fructicola). Initially, the pathogenicity of four types of identified fungi, i.e. C. gloeosporioides, M. fructicola,Fusarium sp. and Curvularia sp. on red dragon fruit was studied. Fully matured fruits (index five) were wounded and inoculated with spore of respective fungi at 108 spore·mL-1. Two days after incubation, 100% of the inoculated fruits were infected by three species of the fungi species tested except those inoculated with Curvularia sp. as well as control fruit. Further experimentation was conducted to study the effect of diseases on fruit quality parameters, involving inoculation of two spore concentrations of C. gloeosporioides and M. fructicola (104 and 106 spores·mL-1). All fruits revealed 100% of infection except in fruit inoculated with 104 spores·mL-1 M. fructicola and control. The disease severity also was dependent on spore concentrations. At higher spore concentration, brown rot disease caused by M. fructicola was more severe compared to anthracnose (caused by C. gloeosporioides), with their respective lesion size at 8.4 and 5.8 cm2 three days after incubation (DAI). Diseased fruits were softer, low in soluble solids contents (SSC), titratable acidity (TA) but higher in pH. Prolonging the incubation period to five days increased the size of disease lesions as well as reduced fruit quality. The disease lesion on fruits inoculated with C. gloeosporioides increased seven times from 9.6 at three DAI to 63.0 cm2 at five DAI. Meanwhile, the disease lesion increased nine times from 10.1 to 91.7 cm2 for M. fructicola. These results show serious damage could arise from the anthracnose and brown rot diseases. Subsequently, the effect of preharvest calcium application on disease occurrence and fruit quality was studied by spraying calcium chloride (CaCl2) solution directly on the fruits at five concentrations (0, 1.0, 2.0, 3.0 and 4.0 g·L-1), at four weekly intervals. Results showed that the severity of anthracnose and brown rot was reduced with increasing Ca concentration. The size of lesions on fruits inoculated with C. gloeosporioides and M. fructicola declined up to 85 % and 91 % as the Ca concentration increased from 0 to 4 g·L-1, respectively. Disease severity was negatively correlated to Ca content in fruit peel (r = - 0.91). Ca application promoted fruit firmness. Ca application at 4 g·L-1 brought firmness of infected fruit to a comparable value to uninfected fruit treated at the same level of Ca. There was no effect of Ca application on pH, SSC and TA of uninfected fruit. However Ca application at higher concentration retained such quality attributes in infected fruit. Similar results were also observed in fruit treated with postharvest dipping at concentrations of Ca; 0, 1.0, 2.0, 3.0 and 4.0 g·L-1. Disease severity of fruits inoculated with C. oeosporioides and M. fructicola was reduced up to 70 % and 65 % as the Ca concentration increased from 0 to 4 g·L-1, respectively. Fruit firmness was increased with increasing Ca concentration either in uninfected or infected fruit. The effect of disease on pH, SSC and TA of fruit was mitigated by Ca application. For the uninfected fruit, Ca dipping had no effect on such quality attributes. Pre- or postharvest Ca application was also successful in elevating fruit Ca content without affecting the uptake of nitrogen (N), phosphorous (P), potassium (K) and magnesium (Mg). In conclusion, Ca application as preharvest spraying or postharvest dipping was successful in reducing disease severity and mitigating the effect of diseases on quality of fruit as well as elevating the fruit Ca content. These findings seemed promising on the use of CaCl2 for shelflife extension and storability of dragon fruits. CaCl2 application could be used as part of the management strategy in reducing anthracnose and brown rot diseases in red flesh dragon fruits.